Depression Tendencies, Social Skills, and Loneliness among College Students in Yogyakarta - Fauziyyah, Alya; Ampuni, Sutarimah (Jurnal Psikologi, 2018)
This research aimed to examine the role of social skills in depression among college students through the mediation of loneliness.Â  As many as 645 college students in Yogyakarta (Male = 180, Female = 465) participated in this study. Social skills were measured using the Social Skills Scale, depression was measured using the Beck Depression Inventory-II (BDI-II), and loneliness was measured using UCLA Loneliness Scale version 3, which were adapted into Bahasa Indonesia. Regression analysis with a simple mediation model showed that, as expected, social skills negatively contributed to depression with the mediation of loneliness. This means that lower social skills were associated with higher loneliness and in turn contributed to an increasing tendency towards depression among college students. Additional analysis found that levels of social skills, loneliness, and depression differed among college students in different years, with students in the fifth years and after being lower on social skills and higher on loneliness and depression. Furthermore, it was shown that 51% of respondents were indicating depression symptoms which levels varied from mild to severe.